A Comparison of Incumbent Regional Expenditure Allocations: Before vs. During The 2024 Regional Head Election - Abdillah, Fauzan Hanif (Jurnal Perpajakan dan Keuangan Publik, 2025)
This study aims to analyze the effect of regional head elections on regional budget allocations in regions led by incumbent regional heads in Java. The analysis was conducted comparatively between budget allocations in the period before the election and the period during the election. The method used was the Wilcoxon signed-rank test to compare the average regional spending allocations, which include grant spending, social assistance spending, goods and services spending, and capital spending. The research sample consisted of 40 districts/cities in Java whose regional heads were running again in the 2024 Regional Head Elections (Pilkada). The results of the study show that incumbent regional heads tend to be opportunistic by utilizing budget discretion for electoral interests. This is reflected in the significant differences in the allocation of grant spending, social assistance, and capital spending between the periods before and during the 2024 election.